(untitled) (Research, Society and Development, 2022)
Objective: To analyze the profile of physiotherapy students from a public institution in Santarém who have musculoskeletal pain, as well as to verify which are the most frequent pains and their degree of intensity. Methodology: This is a descriptive cross-sectional study, with a quantitative approach, developed with Physiotherapy students from the State University of Pará, Campus XII/Santarém. Two instruments were used for data collection, the Nordic Pain Questionnaire, and the Visual Analog Scale of Pain (VAS) with 46 participants. Research approved by the Ethics and Research Committee of the Universidade do Estado do Pará under no. CAEE: 42238621.8.0000.8767. Results: It was observed that most participants are female and have a mean age of 20.7 years, it was also found that among the most prevalent pain among academics, low back pain stood out with 93.48% of the reports, in relation to pain intensity, it was noted that most of the listed pains are mild or moderate, causing discomfort, but not preventing them from performing activities of daily living. Conclusion: It is essential that this issue be treated more seriously by educational institutions, since training is a unique moment of learning, and if the academic is subjected to extreme conditions imposed by the routine between internship and theoretical classes, there comes a time when the university student’s body will begin to show signs of wear and tear and extreme stress.